EVALUATIO OF MICROBIAL AGENTS AND BIO-PRODUCTS FOR THE MANAGEMENT OF MUSTARD APHID, LIPAPHIS ERYSIMI (KALT.) - MEENA, HANSRAJ; S. P. SINGH,; NAGAR, RAJENDRA (The Bioscan, 2013)
Microbial agents (Verticillium lecanii, Beauveria bassiana and Metarhizium anisopliae @ 5 g per litre of water), plant products (Tobacco, onion and neem seed kernel extract @ 5%), cow urine @ 50 litre/ha and dimethoate 30EC @ 300 g a.i/ha were evaluated against mustard aphid, Lipaphis erysimi (Kalt.) and their safety to natural enemies and pollinators. Significantly higher aphid reduction was recorded under these treatments over the control without any phytotoxic effect and found safe to natural enemies of mustard aphid and honeybee. Most favourable cost-benefit ratio was obtained under the treatment i.e. dimethoate 30 EC @ 300 g a.i/ha (1:38) followed by neem seed kernel extract @ 5% (1:18), onion extract @ 5% (1:17), cow urine @ 50 litre/ha (1:11), Beauveria bassiana @ 5 g per litre of water (1:10), Verticillium lecanii @ 5 g per litre of water (1:10), Metarhizium anisopliae @ 5 g per litre of water (1:8), tobacco extract @ 5% (1:6) and water spray (1:2).